Political party development in Mongolia and an analysis of cartel-party patterns - Bayarmagnai, Bayarbaatar; Dagva-Ochir, Bumdari (Technium Social Sciences Journal, 2026)
In this article, building on theories and methodologies related to political parties, party finance, cartel parties, and party cartelization, we examine through quantitative analysis whether state funding of political parties can serve as a means of reducing party cartelization.